Pengaruh Return On Asset, Debt To Equity Ratio dan Deferred Tax Expense Terhadap tax Avoidance - Farah Nabilla Ramadhani; Sri Setia Ningsih (Universitas Muhammadiyah Tangerang, 2022)
Tax avoidance is an activity carried out by taxpayers, in carrying out tax avoidance without conflicting with the law or tax law provisions. This study aims to examine the return on assets, debt to equity ratio and deferred tax expense either partially or simultaneously. The sample of this research used 11 food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The data analysis technique used in this research is multiple linear regression analysis with SPSS software version 25. The results of this research indicate that partially return on assets has a negative and insignificant effect on tax avoidance, debt to equity has a positive and significant effect on tax avidance, deferred tax expense has a negative and insignificant effect on tax avoidance. Simultaneously return on assets, debt to equity ratio and deferred tax expense simultaneously have an effect on tax avoidance of 19,2%, while 80,8% is explained by other factors that aren’t explained by this research.